Efektivitas Pendekatan Spiritual Dalam Pendidikan Agama Islam Untuk Mengurangi Tindakan Bullying Siswa di MAN 1 Mojokerto - Anam, Muhammad Syafi’i (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the effectiveness of the spiritual approach in Islamic Religious Education (PAI) as a strategy to reduce bullying behavior at MAN 1 Mojokerto. Bullying remains a serious issue that disrupts students’ mental and social development. The spiritual approach is chosen because it internalizes Islamic values that strengthen self-awareness, empathy, and self-control among students. Using a descriptive qualitative method through a case study, this research involves PAI teachers, homeroom teachers, and students as subjects. Data collection techniques include interviews, observations, and documentation. The results show that the spiritual approach, implemented through activities such as self-reflection (muhasabah), contemplation (tadabbur), remembrance (dzikir), and thematic sermons, has succeeded in reducing bullying incidents by up to 40% within one semester. Despite challenges such as varying religious backgrounds among students and limited parental support, this approach proves to be more effective than punitive methods. The study recommends strengthening the spiritual approach within the character education curriculum and providing special training for PAI teachers.